(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
This paper is concerned with the existence of positive solutions to nonlinear q-fractional differential equations yielding to the integral boundary value conditions. Under sufficient conditions of the nonlinearity, by using some iterative techniques, we get that this problem has two positive solutions and a unique positive solution respectively. Our results improve some recent work.